Assessing the Effectiveness of a Specialized, Field-Based Treatment Program for Youth Who Have Committed Sexual Offenses in an Australian Jurisdiction - Ogilvie, James M. (International journal of offender therapy and comparative criminology, 2024)
This study provides an evaluation of recidivism outcomes for a specialized, field-based treatment program for youth who perpetrate sexual offenses in an Australian jurisdiction. Using survival analyses, recidivism outcomes for the treatment group (n = 200), who were followed for an average of 5.07 years (SD = 3.13), were contrasted with a sample of sexually offending youth who were either referred but not accepted or not referred to the program (n = 295). Rates of sexual recidivism were low and not significantly different between the groups (9.5% for treated and 10.8% for untreated). Unadjusted Cox regression results indicated that the treated group were less likely to violently recidivate compared to the untreated group (HR = 1.41, 95% CI [1.01, 1.96]), but this effect became nonsignificant when controlling for offense history covariates (HR = 1.22, 95% CI [0.87, 1.72]). Both groups exhibited high rates of nonsexual offending during the follow-up period, and treatment factors including clinician-rated success, were found to be associated with a lower frequency of reoffending after treatment. Findings highlight important considerations for both practice and research. First, findings suggest the need for specialized programs to ensure factors associated with general recidivism are also addressed in treatment; second, findings reinforce potential utility for clinician-rated and structured assessments to inform treatment planning and outcomes. Finally, the findings raise the importance of appropriate comparison groups when designing evaluation studies, to accurately inform policy and practice.